1997
DOI: 10.1192/bjp.171.5.420
|View full text |Cite
|
Sign up to set email alerts
|

London–East Anglia randomised controlled trial of cognitive–behavioural therapy for psychosis

Abstract: Good outcome is strongly predicted in patients with persistent delusions by a cognitive measure, while this was not the case in controls. Thus we argue that positive outcome in CBT is due in part to specific effects on delusional thinking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
125
0
6

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 268 publications
(141 citation statements)
references
References 17 publications
10
125
0
6
Order By: Relevance
“…We would also highlight two other factors that have received less experimental attention. First, we have obtained evidence that a lack of belief flexibility (the willingness to consider alternatives to delusional beliefs) is associated with poorer outcome, independent of the severity of the delusion (Garety et al 1997). Secondly, the normal belief confirmation bias is likely to maintain psychotic beliefs (Maher, 1974).…”
Section: A Cognitive Model Of Psychosismentioning
confidence: 98%
See 1 more Smart Citation
“…We would also highlight two other factors that have received less experimental attention. First, we have obtained evidence that a lack of belief flexibility (the willingness to consider alternatives to delusional beliefs) is associated with poorer outcome, independent of the severity of the delusion (Garety et al 1997). Secondly, the normal belief confirmation bias is likely to maintain psychotic beliefs (Maher, 1974).…”
Section: A Cognitive Model Of Psychosismentioning
confidence: 98%
“…Standard assessments of insight are only modestly correlated with outcome (David, 1998). However, insight is correlated with the ' belief maintenance ' subscale of the Maudsley Assessment of Delusions, and improved outcome for delusions in response to CBT is associated with and predicted by changes in the MADS subscale (Garety et al 1997). Also important are appraisals of the experience of chronic mental illness as stigmatizing and humiliating, appraisals which may influence the development of depression (Birchwood & Iqbal, 1998).…”
Section: Dysfunctional Schemas and Adverse Social Environmentsmentioning
confidence: 99%
“…The present study, as well as one other study of CBT for psychosis (Leclerc et al 2000), found that neuropsychological impairment did not significantly moderate outcome in CBT relative to standard care. Further, more severe neuropsychological impairment was associated with better symptom outcome in another study of CBT for psychosis (Garety et al 1997). Published research, therefore, has provided no support for the assumption that people with neuropsychological impairment should be excluded from CBT for psychosis.…”
Section: Discussionmentioning
confidence: 96%
“…One study of CBT for psychosis (Leclerc et al 2000) found that attention and learning and memory did not moderate outcome in CBT relative to standard care. Another study of CBT for psychosis (Garety et al 1997), found that only one of four neuropsychological tests was a significant moderator of symptom outcome, but the finding was counter-intuitive: More severe neuropsychological impairment was associated with better symptom outcome.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation